Parallel Implementation of a Two-level Algebraic ILU(k)-based Domain Decomposition Preconditioner - Nievinski, Italo Cristiano L.; Souza, Michael; Goldfeld, Paulo; Augusto, Douglas Adriano; Rodrigues, José Roberto P.; Carvalho, Luiz Mariano (Trends in Computational and Applied Mathematics, 2018)
We discuss the parallel implementation of a two-level algebraic ILU(k)-based domain decomposition preconditioner using the PETSc library. We present strategies to improve performance and minimize communication among processes during setup and application phases. We compare our implementation with an off-the-shelf preconditioner in PETSc for solving linear systems arising in reservoir simulation problems, and show that for some cases our implementation performs better.